IIntersections of jazz and art : exploring curatorial methodologies in Sam Nhlengethwa's 1994 and 2010 exhibitions through synaesthesia and exhibitionary affect - Tlhoaele, Boitumelo (My University, 2017)
The objective of this study it to understand the intersections between jazz and art and what this means in the context of curatorial practices that focus on jazz as its theme. Its focus is to explore curatorial methodologies found in visual artist Sam Nhlengethwa’s exhibitions Sam Nhlengethwa: Standard Bank Young Artist Award (1994) and Kind of Blue (2010), through the implementation of two theories, namely Syneasthesia and Exhibitionary Affect. These theories are applied as an interdisciplinary inquiry to investigate Nhlengethwa’s exhibitions and suggest this to be an effective way of not only analysing but re-imagining these exhibitions. This study asks for a consideration of the notion that beyond the object is the impact of ambience (exhibitionary affect) in an exhibition, and considers the meeting points of jazz and art. This is first achieved by understanding synaesthesia in art and to what extent this speaks to Nhlengethwa’s artistic practice and his exhibitions, and then, to what extent synaesthesia is intertwined with notions of exhibitionary affect and the way these theories propose for curatorial methodologies of jazz exhibitions through the analysis of these case studies. The use of these theories have been motivated by the links between jazz and art and the way this relationship has existed within the visual arts globally since as far back as the nineteenth century. Artists of this period and beyond have factored music in their art and tried to assimilate musical qualities in their work. Jazz too has been a subject of inquiry for visual artists with quite a number of exhibitions drawing on jazz as a theme, and being staged as a result. But what does it mean to curate a jazz exhibition and in what ways can this happen through synaesthesia and exhibitionary affect?
This thesis is submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Arts in Heritage Studies by Course Work and Research Report.
Keywords: Painters--South Africa; Art, Modern--20th century